Effect of Community Based Organization microcredit on livelihood improvement (Journal of the Bangladesh Agricultural University, 2011)
The study was conducted to examine the effects of Community Based Organization (CBO) micro-credit program of Concern Worldwide on the livelihood improvement of beneficiaries in a selected area of Mymensingh district. In the study, 50 respondents were purposively selected of which 30, 12 and 8 were engaged in small trading, saloon and rickshaw pulling respectively. Tabular and statistical analyses were applied for achieving the objectives. All of the factors to measure the socio-economic condition such as awareness, family income, assets, clothing, etc has been changed. It was also found that the women participation in the household decision making increases. Repayment performance of CBO micro-credit program was highly satisfactory. Respondent’s income and loan receipt amount were positively contributed to loan repayment, whereas respondent’s age, education, family size and forced saving negatively affected the same. Ninety four per cent of the respondents mainly repaid their loan on time with the hope of getting loan in future. Overall, the CBO micro-credit program was found to have significant positive effects on livelihood improvement. Keywords: CBO; Micro credit; Concern Worldwide; Livelihood Improvement DOI: 10.3329/jbau.v8i2.7938 J. Bangladesh Agril. Univ. 8(2): 277-282, 2010